Pengaruh Core Stability Exercises Dengan Metode Bobath Terhadap Keseimbangan Pada Pasien Stroke Di Poli Irm Rsud Salatiga - Sufiya, Zakiyah; , Isnaini Herawati, S.Fis, M.Sc (2017)
Several post-stroke patients at the policlinic's medical rehabilitation department of the Salatiga regional hospital reported significant balance issues, i.e. falls, they would experience when doing physical activities. To identify any impacts of the core stability exercises using the Bobath method on the post-stroke patients' balance level. To offer an alternative way for researchers to deliver positive impacts and to overcome problems reported by the post-stroke patients at the policlinic's medical rehabilitation department of the Salatiga regional hospital. This study was a quasi-experiment with two groups. It employed pre-test and post-test designs, i.e. the sample of the treatment group conducted the core stability exercises for four weeks, three times per week. The patients' balance were measured by the Tinetti test. The data were analyzed using the Wilcoxon Test to test any impacts and the Mann-Whitney Test to test the difference of the impacts. The impacts of the core stability exercises on the post-stroke patients' improved balance were found after the Wilcoxon Test was conducted which resulted in p-value of 0,005for the treatment group and p-value of 0,027 for the control group. There was difference in the impacts between the treatment group and the control group on the post-stroke patients' improved balance after the Mann-Whitney Test was conducted which resulted in p-value of 0,000. There existed the impacts of the core stability exercises on the post-stroke patients' balance.